SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PENDAKIAN GUNUNG TERBAIK DI JAWA TENGAH MENGGUNAKAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) - Wahyu Hadikristanto; Gatot Tri Pranoto (LPPM Universitas Abdurrab, 2023)
The level of interest in mountain climbing activities has increased significantly, this is inseparable from the development of social media technology which exposes the charm of each mountain itself, so as to attract interest in climbing from various groups, both beginners and experienced. Because each climber has their own characteristics and needs and each mountain also has its own character, so that it will affect each climbing destination, prospective climbers must be able to determine which mountain will be chosen as the best mountain in Central Java province to be chosen. as a climbing location. This research uses secondary data, the alternative to be compared is a list of mountains in Central Java province with several criteria to be used. The method for processing data is the Simple Additive Weighting (SAW) method. This method is used to find the weighted sum and rating of each alternative and all attributes. The results of this study can be a reference for climbers in determining the best mountain to be used as a climbing location in Central Java province.